We - Herrré, Henri (United States, 2010)
Verzio FF submission In 1995 in Dorchester, a neighbourhood of Boston, a new principal was appointed to a local public elementary school. The school and the neighbourhood had been struggling with many issues, including a high percentage of non-English speaking families and occasional violent crime in the area. The principal, along with some dedicated families, decided to create a fully inclusive school - integrating children with mild, moderate and severe disabilities. By 2008, the school had become one of the best, and most requested, elementary schools in the city. Integrating two groups perceived to be the most problematic to deal with - immigrants and the disabled - the school had succeeded. A miracle? Hardly. This film is about their efforts.